Therapeutic Management of Ocular Ischemia in Takayasu’s Arteritis: A Case-Based Systematic Review - Zeng, Yue; Duan, Jianan; Ge, Ge; Zhang, Meixia (Frontiers in Immunology, 2022)
BACKGROUND: Takayasu’s arteritis (TA) is a rare, chronic granulomatous large-vessel vasculitis that can lead to ocular ischemia. Ocular outcomes after therapeutic management in TA remains largely unknown. We herein conduct a case-based systematic review to address the current treatment options in this particular cohort. METHODS: PubMed, Medline and EMBASE databases were searched pertaining to ocular outcomes after systemic treatment in TA. Studies reporting ocular examinations before and after treatment in TA patients with ocular ischemia were included. Clinical characteristics, therapies, ocular outcomes and complications were recorded. RESULTS: A 29-year-old woman with newly diagnosed TA showed dramatic regression of Takayasu’s retinopathy (TR) following balloon angioplasty. Optical coherence tomography angiography (OCTA) was used as a novel strategy for subsequent follow-up. A total of 117 eyes of 66 patients with a median age of 27 years were included for systematic review. TR was the most common ocular manifestation. Oral steroids were prescribed in nearly all patients (n = 65), followed by the use of methotrexate and antiplatelet therapy. 65.8% and 34.2% of patients underwent open surgery and endovascular procedure, respectively. Median follow-up period was 12 weeks (interquartile range 8-33.5). Surgical therapy showed better ocular improvement (including visual and imaging responses) in both acute and chronic vision loss, along with less complications than medical therapy alone. In the surgical group, visual prognosis was significantly better in patients with initial visual acuity better than 20/200 (p = 0.03) and those who underwent surgery before stage III TR (p = 0.01). Ocular outcomes were equivalent comparing the two surgical approaches. CONCLUSION: Clinicians should be familiar with ophthalmic manifestations of this potentially treatable complication in TA. Compared to medical therapy alone, surgical intervention might be a better choice for both acute and chronic vision loss. Surgery is best recommended before the onset of irreversible ischemia to the globe. A combined regimen (oral steroids, immunosuppressants and anti-platelet drugs) might be effective for those with surgical contradictions or reluctance to invasive procedure. Physicians should be aware of the importance of ocular examinations, including OCTA, during the diagnosis and follow-up in TA.